'It's . . . forward-focused': Experiences of a mobility clinic for people with limb loss. (December 2019) - Anderson, Sarah; Chaffey, Lisa; Dillon, Michael
Background: Mobility clinics are designed to extend gait and mobility training beyond rehabilitation programmes. No research has been undertaken into participants' experiences of attending these multidisciplinary, experience-based clinics. Research in this area is needed to ensure clinics meet intended goals, including understanding the motivation and experience of attendees. Insights may improve mobility clinics and inform strategies to encourage greater participation. Objectives: To explore the motivation of people with limb loss to attend a mobility clinic, the experience of participation and their perception of the clinic's benefits. Study design: Qualitative methodology, naturalistic enquiry. Methods: Semi-structured interviews were conducted with nine clinic attendees during the clinic. Interviews were transcribed verbatim, data thematically analysed and emergent themes underwent member checking. Results: Three themes emerged from the data: facing the challenge captured how participants' have adapted to amputation, valuing peers highlights the important role of peers in learning and support and improving mobility described the ongoing quest to improve mobility. Conclusion: The mobility clinic was attractive to those who liked challenges and was an invaluable source of learning for those wishing to improve their mobility. Future clinics should ensure that peer education is supported, and activities cater for a range of skills and fitness levels. Clinical relevance: Findings of this study indicate that those who attended the mobility clinic liked to challenge themselves. Participation with peers was an important source of learning and support. Those participants who had previously attended a mobility clinic reported improvements in their overall daily function.